Collective Action and Football Fandom A Relational Sociological Approach - Cleland, Jamie (Palgrave Studies in Relational Sociology, 2018)
This book draws upon a relational sociological paradigm to explore the processes of collective action in football fandom across Europe and the UK. Through a range of case studies, the authors address pertinent themes in football fandom, including anti-discrimination, 'home,' ticketing, name changes, 'ownership,' and broader leftist politics. Each of these case studies engages with the theoretical framework of cultural relational sociology, highlighting the different social and cultural changes English and European football has undergone, often over a very short period of time. .